Refrigerated storage period of Rhizophores for Yacon propagation (Bioscience Journal, 2020)
Yacon, is known for its tuberous roots, which are consumed as functional food and is propagated mostly in the vegetative form, via propagules, so-called rhizophores. However, they are organs with little durability in its propagation form. Storing them in cold chamber conditions, can be a viable alternative for the seedlings production of the culture. The objective of this study was to verify the influence of the refrigerated storage period of yacon rhizophores in the initial plant development. The experimental design was completely randomized with eight replicates and six treatments and the rhizophores were place in the refrigerated storage for: 7, 14, 21, 28 and 35 days; and time zero (planting without storage). The results show that the rhizophores in the refrigerated storage in a temperature of 8 to 10°C, for a period between 21 to 35 days had better sprouting rate (speed and vigor), reducing mortality, which favored the initial yacon growth. The refrigerated storage between 21 and 35 days showed to be an alternative that resulted in a uniform plant stand in crops, also reflecting the uniformity in the harvest, and minimizes the problem of seasonality offering culture propagation material.